PLASMA-RICH PLATELETS ANTI-INFLAMMATORY EFFECT IN CONDITIONS OF CARRAGEENAN-INDUCED PAW EDEMA IN RATS - Vastyanov, R.S.; Stoyanov, O.M.; Babienko, V.V.; Hruzevskiy, O.A.; Talalayev, K.O.; Kirchev, V.V.; Dvornyk, I.L. (World of Medicine and Biology, 2024)
The purpose of the study was to determine the expression of platelet-rich plasma anti-inflammatory effect in conditions of its complex use in a model of carrageenan-induced paw edema in rats. Experimental studies were performed in conditions of carrageenan-induced exudative aseptic inflammation. Rats were undergone to separate and combined platelet-rich plasma and ellagic acid injections. Diclofenac sodium was used as a reference drug. The inflammatory response indexes, pro-inflammatory cytokine content, and inducible NO-synthase activity in the paw tissue of animals were determined 30 min, 1, 2, 4, and 6 hours after carrageenan administration. The data obtained revealed rats’ hind paw edema reduction, an inflammatory index decrease, and TNF and IL-1β release block after platelet-rich plasma and ellagic acid combined administration in conditions of carrageenan-induced aseptic inflammation. The investigated compound's anti-inflammatory effect was maximal at the delayed stages of inflammatory reaction, starting from 4 hours until the end of the trial. The authors proved the principal possibility of anti-inflammatory efficacy increasing as a result of platelet-rich plasma and ellagic acid combined administration in the form of additivity. The possibility of anti-inflammatory efficacy increasing by platelet-rich plasma added to a complex pharmacological regimen was demonstrated. The revealed platelet-rich plasma and ellagic acid combined administration anti-inflammatory efficacy and a pathogenetic background of this protective effect implementation in carrageenan-induced rat paw inflammation prove the reasonability of this pharmacological scheme anti-inflammatory efficacy clinical testing.
Keywords: aseptic inflammation; carrageenan; rats; paw edema; ellagic acid; platelet-rich plasma; pathophysiological mechanisms; pathogenetically oriented pharmacocorrection